Evaluation of in vitro storage properties of apheresis platelets suspended in a bicarbonate‐containing additive solution with low levels of plasma and stored with a 24‐hour interruption of agitation. Issue 4 (12th December 2013) - Skripchenko, A.; Turgeon, A.; Thompson‐Montgomery, D.; Awatefe, H.; Wagner, S. J.
<x xml:space="preserve">Abstract</x> Background and Objectives PLT additive solutions (PAS) are useful for reducing the frequency and/or severity of plasma‐associated transfusion reactions. A new PAS solution, PAS‐5, containing 5% plasma, maintains in vitro PLT properties during 7‐day storage. Periods with interruption of agitation (IA) ≤24 h routinely occur during PLT shipment and do not usually compromise platelet quality. The aim of the study was to evaluate the properties of PLTs stored for 7 days in 95% PAS‐5/5% plasma subjected to a 24‐h IA. Materials and methods Double apheresis Amicus units (n = 12) were collected using a manual PAS‐5 addition to hyperconcentrated PLTs. PLT units were equally divided in two containers. Control and test PLTs were stored with continuous agitation at 20–24°C except for 24‐h IA period for test units between days 2–3. Results During storage, levels of glucose, lactate, mitochondrial membrane potential and aggregation significantly differed in test units compared to those of control. The pH levels of test PLTs were less than those of control units with 7/12 test units having pHs <6·2 on Day 7 compared to 1/12 control units. Morphology score, GP1bα expression, ESC values, superoxide production were also less, and activation was greater in test PLTs than those of control. All other parameters were similar between test and control units. Conclusion PLTs stored in PAS‐5 solution containing 5% plasma with a 24‐h IA results in marked decrements in many in vitro PLT quality parameters during 7‐day storage.